2009
DOI: 10.1080/10495390903381792
|View full text |Cite
|
Sign up to set email alerts
|

Expression Studies of the Obesity Candidate GeneFTOin Pig

Abstract: Obesity is an increasing problem worldwide and research on candidate genes in good animal models is highly needed. The pig is an excellent model as its metabolism, organ size, and eating habits resemble that of humans. The present study is focused on the characterization of the fat mass and obesity associated gene (FTO) in pig. This gene has recently been associated with increased body mass index in several human populations. To establish information on the expression profile of FTO in the pig we performed qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…The levels of FTO transcript in the cerebellum of high-cholesterol fed pigs were significantly higher than the controls. 39 Also, in human and rat, FTO had the nearly high expression in the cerebellum and hypothalamus. 37 The large impact of fasting and high-glucose/fat diets on cFTO1 and PGC1a expression strongly suggest a role of FTO in glucose and energy metabolism in the chicken.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of FTO transcript in the cerebellum of high-cholesterol fed pigs were significantly higher than the controls. 39 Also, in human and rat, FTO had the nearly high expression in the cerebellum and hypothalamus. 37 The large impact of fasting and high-glucose/fat diets on cFTO1 and PGC1a expression strongly suggest a role of FTO in glucose and energy metabolism in the chicken.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Huang et al, 2010;Madsen et al, 2010) showed the FTO mRNA could be expressed in most pig tissues, including muscle. In our study, different breeds showed different patterns of FTO mRNA expression in longissimus dorsi muscle tissue.…”
Section: Discussionmentioning
confidence: 98%
“…Although previous studies have investigated FTO mRNA expression in the brain and adipose tissue, few papers have reported FTO expression characteristics in porcine muscle (Huang et al, 2010;Madsen et al, 2010). In humans, FTO mRNA expression in skeletal muscle has been demonstrated to be regulated by both age and sex, and is negatively correlated with fat deposition (Klöting et al, 2008;Grunnet et al, 2009).…”
mentioning
confidence: 99%
“…In mammals, FTO expression has been detected in hypothalamus adipose tissue and the liver (Fredriksson et al, 2008;Stratigopoulos et al, 2008;Madsen et al, 2010). In the rat, fasting reduces levels of FTO mRNA in the arcuate nucleus of the hypothalamus, a site where FTO expression is particularly high (Tung et al, 2010).…”
Section: Discussionmentioning
confidence: 99%